Factors affecting prehospital delay in rural and urban patients with stroke: a prospective survey-based study in Southwest Germany - Ungerer, Matthias; Busetto, Loraine; Haji Begli, Nima; Riehle, Katharina; Regula, Jens Ulrich; Gumbinger, Christoph (BMC neurology, 2020)
Reducing prehospital delay plays an important role in increasing the thrombolysis rate in patients with stroke. Several studies have identified predictors for presentation ≤4.5 h, but few compared these predictors in urban and rural communities. We aimed to identify predictors of timely presentation to the hospital and identify possible differences between the urban and rural populations.